Dampak Faktor Individu dan Pekerjaan terhadap Tingkat Stres Kerja di Perusahaan Makanan dan Minuman - Maharani, Adhella; Karima, Ulya Qoulan; Fithri, Nayla Kamilia; Amrullah, Afif Amir (Health Safety Environment, 2024)
Background: Preliminary studies show that over 50% of those interviewed experience mild stress. This company operates in the food and beverage sector, a business demanding considerable attention, stress, and pressure amidst company growth. This sector remains underexplored in terms of understanding and reinforcing factors causing stress on individuals and specific jobs. This study aims to determine the relationship between individual and job-related factors on work stress. Methods: This cross-sectional study includes PT X employees as the research population, conducted from May to June 2024. Using purposive sampling, the sample size consists of 60 respondents. Research instruments include the Workplace Stress Scale, Job Demands Questionnaire, NASA Task Load Index (TLX), and Coworker Support Scale. Data analysis utilizes the Chi-square bivariate correlation test. Results: The findings indicate that approximately 36.7% of employees experience no work stress, 30% experience mild work stress, and 5% experience high work stress. No significant relationship was found between gender (p = 0.943), age (p = 0.874), education level (p = 0.218), years of service (p = 0.218), mental workload (p = 0.196), job demands (p = 0.109), or coworker support (p = 0.288) and work stress. Conclusion: This study reveals no significant relationship between individual and job-related factors and work stress, suggesting that additional factors such as job control, interpersonal communication, and mindfulness may require further investigation. Keyword : Work Stress, individual factors, work factors